2018
DOI: 10.1002/pssa.201800270
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Study of Vibrational and Luminescence Properties of Zn2GeO4 Microrods

Abstract: The optical properties of zinc germanate microrods are investigated and correlated with vibrational modes of the crystalline structure. The samples are grown by a thermal evaporation method using ZnO and Ge as precursors. Polarized Raman spectroscopy and polarized micro‐photoluminescence techniques are applied in order to shed some light into the origin of the luminescence in Zn2GeO4. Oxygen defects are usually responsible for light emission in most of semiconducting oxides. Here, the authors report two lumine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The apparently shift of the visible band could be associated to changes in the ratio among their components, affecting most to the 2.44 eV component. This effect has also been observed in undoped samples and it has been linked to oxygen vacancies [17] . Concerning the UV emission, a clear shift to higher energies is detected by recording polarized light parallel to the microwire axis.…”
Section: Raman Modementioning
confidence: 64%
See 1 more Smart Citation
“…The apparently shift of the visible band could be associated to changes in the ratio among their components, affecting most to the 2.44 eV component. This effect has also been observed in undoped samples and it has been linked to oxygen vacancies [17] . Concerning the UV emission, a clear shift to higher energies is detected by recording polarized light parallel to the microwire axis.…”
Section: Raman Modementioning
confidence: 64%
“…Raman spectra from undoped samples showed that relative intensity between modes changed as a function of the particular polarization orientation between the laser and the microwire. In particular, total and partial quenching of E g (4) and E g (3) modes, respectively, both perpendicular to c-axis, were attributed to the orientation of the wire along c-axis [17] . Figure 3 mode, related to vibration modes in O-Ge-O, it could be possible that Mg ions sited at Zn lattice locations would do not affect this mode, and, hence its dependence on the polarization conditions is the same that in the undoped case.…”
Section: Resultsmentioning
confidence: 97%
“…Figure 1b shows Raman peaks representative of the rutile phase of SnO 2 corresponding to the E g (478 cm −1 ), A 1g (634 cm −1 ) and B 2g (778 cm −1 ) vibration modes [5]. On the other hand, figure 1c shows the characteristic Raman peaks of the rhombohedral structure of Zn 2 GeO 4 (745, 751, 777 and 802 cm −1 ) associated with Ge-O-Zn symmetric and asymmetric vibration modes and the O-Ge-O bending and stretching modes [6,7]. The 520 cm −1 peak corresponds to the silicon substrate.…”
Section: Resultsmentioning
confidence: 98%
“…ZnO:Ge (1:1) precursors produces a huge white mat of structures after the dynamic thermal annealing that fully cover the substrate, as it can be observed in the optical image and in the secondary electron (SE) image of Figure 1a. The thermal treatment of the T(21) pellet produces as well similar Zn 2 GeO 4 microrods; however, the density of microstructures over the pellet is lower than in T (11). Figure 1b,c shows SE images with the detail of some Zn 2 GeO 4 microrods, in which most of them appear to exhibit a hexagonal cross-section shape.…”
Section: Introductionmentioning
confidence: 96%
“…In contrast, the influence of growth conditions on the equilibrium defect concentration and samples architecture has been appeared to play a critical role in the luminescence properties of Zn 2 GeO 4 . [4,[9][10][11][12] Thermal annealing of precursor materials containing Zn and Ge has been revealed as an effective method to produce high-quality crystalline Zn 2 GeO 4 microrods and nanowires under the vapor-solid mechanism. [5,13] In particular, luminescence in the UV and in the visible range depending on the probe energy, above of below the energy bandgap, has been observed in Zn 2 GeO 4 microrods synthetized by a thermal treatment of a mixture of ZnO and Ge.…”
Section: Introductionmentioning
confidence: 99%